Transforming Physical Education and Sports Coaching: Integrating Modern Teaching Strategies for Athlete Development - Herman Syah, Maulidin (Lembaga Bale Literasi, 2025)
The rapid evolution of sport pedagogy has shifted physical education and sports coaching from traditional coach-centered instruction toward learner-centered, technology-enhanced, and holistic approaches to athlete development. However, limited research has integrated these complementary pedagogical strategies into a comprehensive coaching framework. This study aimed to examine how modern teaching strategies can be systematically integrated to enhance coaching effectiveness and promote holistic athlete development. A qualitative descriptive research design was employed involving 24 purposively selected participants, comprising physical education lecturers, certified sports coaches, physical education teachers, and student-athletes. Data were collected through semi-structured interviews, non-participant observations, and document analysis and were analyzed using thematic analysis following the interactive model of Miles, Huberman, and Saldaña. Methodological triangulation, member checking, and peer debriefing were employed to enhance the credibility and trustworthiness of the findings. The analysis identified five interrelated themes: learner-centered pedagogy, athlete-centered coaching, digital coaching technologies, collaborative learning, and holistic athlete development. Frequency analysis revealed that holistic athlete development and learner-centered pedagogy were the most prominent themes, while triangulation demonstrated strong consistency across interviews, observations, and documentary evidence. The findings indicate that learner-centered instructional practices increase athlete engagement, individualized coaching enhances motivation and autonomy, digital technologies facilitate timely and evidence-based performance feedback, and collaborative learning strengthens communication and teamwork. Collectively, these pedagogical strategies foster multidimensional athlete development encompassing physical, cognitive, psychological, social, and ethical competencies. The study concludes that integrating learner-centered pedagogy, athlete-centered coaching, collaborative learning, and digital technologies provides a robust evidence-based framework for transforming contemporary physical education and sports coaching. This integrated approach contributes to improved coaching effectiveness and supports sustainable, holistic athlete development across diverse educational and sporting contexts.